2021
DOI: 10.1021/acsomega.1c03008
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Nanoclay-Surfactant-Stabilized Foam for Improving Oil Recovery of Steam Flooding in Offshore Heavy Oil Reservoirs

Abstract: This study presents a study of nanoclay-surfactant-stabilized foam to improve the oil recovery of steam flooding in offshore heavy oil reservoirs. The foam stability and thermal resistance studies were first performed to investigate the influence of nanoclay on the stability and thermal resistance properties of the foam system. Then, the sandpack flooding tests were conducted for investigating the resistance factor and displacement abilities by nanoclay-surfactant-stabilized foam. The results showed that the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…Thus, the resistance factor of nanoclay–surfactant-stabilized foam with different gas-to-liquid ratios shows the highest value at high temperatures. This indicates that the foam has good ability to change the profile and blocking . Additionally, stable N 2 foams has been successfully created utilizing various surfactants and silica NPs, with the durability of the foam being tested by bulk foam stability tests .…”
Section: New Generation Np-stabilized Foam In Oil Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the resistance factor of nanoclay–surfactant-stabilized foam with different gas-to-liquid ratios shows the highest value at high temperatures. This indicates that the foam has good ability to change the profile and blocking . Additionally, stable N 2 foams has been successfully created utilizing various surfactants and silica NPs, with the durability of the foam being tested by bulk foam stability tests .…”
Section: New Generation Np-stabilized Foam In Oil Recoverymentioning
confidence: 99%
“…This indicates that the foam has good ability to change the profile and blocking. 180 Additionally, stable N 2 foams has been successfully created utilizing various surfactants and silica NPs, with the durability of the foam being tested by bulk foam stability tests. 181 Therefore, the results demonstrated that utilizing surfactant, nitrogen, and nanoclay, in conjunction with SiO 2 , for CO 2 foam flooding can increase the oil recovery.…”
Section: New Generation Np-stabilized Foam In Oil Recoverymentioning
confidence: 99%
“…Для повышения нефтеотдачи при закачке пара в морские резервуары с тяжелой нефтью проведены исследования пены, стабилизированной наноглиной и ПАВ [34]. Испытания на модели песчаника показали, что пена, стабилизированная наноглиной и ПАВ, может эффективно отводить пар в область с низкой проницаемостью и повышать эффективность охвата, тем самым улучшая добычу тяжелой нефти при заводнении паром.…”
Section: пены стабилизированные наночастицамиunclassified
“…The development difficulties of offshore heavy oil reservoirs are mainly deep buried reservoir, high porosity, fine lithology, thin single layer and complex oilwater relationship, resulting in high steam injection pressure, large heat loss, small steam spread range and poor development benefit, which makes CO2 occupy a certain position in EOR of such reservoirs, which also provides good storage conditions for CO2 storage [4] .…”
Section: Introductionmentioning
confidence: 99%